2016
DOI: 10.3892/mmr.2016.5695
|View full text |Cite
|
Sign up to set email alerts
|

Effects of endomorphin-1 postconditioning on myocardial ischemia/reperfusion injury and myocardial cell apoptosis in a rat model

Abstract: Endomorphins (EMs) have important roles in the body with regards to analgesia, feeding behavior, gastrointestinal movement and inflammatory reaction. Recent studies have reported that EMs may also participate in chronic hypoxia in the protection of rat myocardial ischemia/reperfusion; however, the mediator and underlying mechanisms remain to be elucidated. The aim of the present study was to investigate the effects of EM‑1 postconditioning on myocardial ischemia/reperfusion injury (MIRI) and myocardial cell ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…NO, the main effect of the expansion of blood vessels, attenuates myocardial ischemia (22). SOD can resist cell damage caused by oxygen free radicals and timely repair of damaged cells, reflecting the body's ability to clear free radicals, in particular, to reflect the capacity of clearing superoxide anion (23). Increased levels of NO and SOD partly contribute towards the action of DIM to attenuate cardiomyocyte hypoxia injury.…”
Section: Discussionmentioning
confidence: 99%
“…NO, the main effect of the expansion of blood vessels, attenuates myocardial ischemia (22). SOD can resist cell damage caused by oxygen free radicals and timely repair of damaged cells, reflecting the body's ability to clear free radicals, in particular, to reflect the capacity of clearing superoxide anion (23). Increased levels of NO and SOD partly contribute towards the action of DIM to attenuate cardiomyocyte hypoxia injury.…”
Section: Discussionmentioning
confidence: 99%
“…For the control group, 2 mL of DMEM/F-12 medium containing 10% FBS was added to the 6-well plate. [25][26][27][28][29][30][31][32][33][34][35] and 10% FBS containing NSC-CPM were added to the 6-well plate, with the final concentration of Aβ 25-35 40 µM. The isolation and culturing of the NSCs and the NSC-CDM were performed according to our previous study [12].…”
Section: Cell Culture and Treatmentmentioning
confidence: 99%
“…In addition, the protective effect of ischemic postconditioning is comparable with that of IP. On the other hand, accumulating evidence has shown that drug treatments for ischemic myocardium at the onset of reperfusion (e.g., pharmacological postconditioning) are capable of providing a similar protective effect with ischemic postconditioning [6-9]. Pharmacological postconditioning represents an ideal alternative for ischemic postconditioning since its clinical operation is simpler than ischemic postconditioning.…”
Section: Introductionmentioning
confidence: 99%